Malaysian tourists’ intention to travel during the Covid-19 pandemic/ Nor Syuhada Zulkefli ... [et al.] - Zulkefli, Nor Syuhada; Mohd Radzol, Aifa Rozaini; Abdul Rahim, Marlisa; Hashim, Hazzyati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study aimed to analyse what drives the Malaysian population and the implications of decision-making on travel intentions during the Covid-19 pandemic. The study addressed the modulating effects of decision-making, namely attitudes, perceived behaviour control (PBC) and social norms on the intention to travel by applying the Theory of Planned Behaviour (TPB). The study also examined additional measures on the willingness to pay for safety measures during travelling amid the pandemic situation. The research process involved 330 respondents who filled online self-administrated questionnaires. The framework was tested using the Partial Least Square Structural Equation Modelling (PLS-SEM) software. The PBC has the most notable effect on travel intention compared to other variables. Furthermore, the empirical results can contribute to developing safety measures in tourism services and designing effective actions to restore tourism. This study sets a significant of research agenda for future tourism research by understanding the mechanisms underlying crisis perceptions and tourist behaviour.